Customer Satisfaction As A Mediator of The Influence of E-Marketing on Brand Image In XYZ Company - Ridwan Ramadhan; Sofiati, Nunung Ayu; Sudaryo, Yoyo; Ali, Mochamad Mukti; Alfarisi, Ade Salman; Luntungan, Irving Ignatius Paul; Sakti, Anggono Raras Tirto (Dinasti Publisher, 2025)
This study aims to analyze Customer Satisfaction as a mediator of the influence of E-Marketing on Brand Image at PT. XYZ E-Marketing, which includes Information, Service Existence, Service Responsiveness, Purchase Transaction Process, and Usefulness, has been well owned by the company. Customer Satisfaction, which includes the dimensions of Product Quality, Service Quality, and Price, is at a satisfactory level, while Brand Image, which includes Reputation, Recognition, Affinity, and Brand Loyalty, is also considered good by customers. With the cluster random sampling technique, a sample of 150 respondents was obtained from a population of 1,235 customers. Based on SEM analysis using the LISREL 8.80 program, the results showed that E-Marketing has a significant partial influence on Customer Satisfaction of 51.2% and on Brand Image of 17.3%. While Customer Satisfaction has a significant partial influence on Brand Image of 30.1%. Furthermore, from the Sobel test, it is known that Customer Satisfaction has a significant influence in mediating the E-Marketing Mix on Brand Image, with a mediator influence of 15.5%. This finding highlights the importance of optimizing E-Marketing strategies to increase Customer Satisfaction and strengthen Brand Image in the eyes of customers.